Depression is the most significant independent predictor of fatigue in patients with primary Sjögren’s syndrome - Koray Ayar; Meliha Kasapoğlu Aksoy; Tülay Dilara Hattatoğlu; Büşra Yeşil (Archives of Rheumatology, 2023)
Objectives: The study aimed to evaluate the level of fatigue and the relationship between mood, pain, fibromyalgia, insomnia, disease activity, and dryness with fatigue in primary Sjögren’s syndrome (PSS) patients. Patients and methods: In this case-control study, the participants were recruited between January 2021 and July 2021. Functional Assessment of Chronic Illness Therapy Fatigue (FACIT-F), pain DETECT questionnaire, Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), Insomnia Severity Index (ISI) were administered to 50 PSS patients (48 females, 2 males; mean age: 48.9±10.8 years; median age: 47 years; range, 29 to 71 years) and 60 healthy controls (HCs; 57 females, 3 males; mean age: 49.8±8.4 years, median age: 52 years; range, 32 to 72 years). In addition, EULAR Sjögren’s syndrome disease activity index (ESSPRI), EULAR Sjögren’s Syndrome Patient Reported Index (ESSDAI), pain thresholds, Schirmer tests, and whole unstimulated salivary flow rate measurements were determined in PSS patients. Independent predictors of fatigue (fatigue subscale scores <30.5) were investigated by logistic regression analysis. Results: The frequency of fatigue in PSS patients and HCs was 54.0% and 8.3%, respectively. The rates of mood disturbance (BDI ≥11) in PSS patients with and without fatigue were 70.4% and 13.1%, respectively. BDI (Rho=-0.804), BAI (Rho=-0.586), ISI (Rho=-0.483), and ESSDAI (Rho=-0.345) were negatively correlated with the fatigue subscale score. Depression [Odds ratio (OR): 1.214, confidence interval (CI): 1.007-1.463], fibromyalgia (OR: 21.674, CI: 1.470-319.469), disease activity (OR: 1.440; CI: 1.005-2.065), and insomnia (OR: 1.223, CI: 1.003-1.4922) were identified as independent predictors of fatigue in PSS patients. It was determined that BD alone could predict fatigue by 84% in PSS patients. Conclusion: Depression can be a prominent predictor of fatigue in PSS patients. There is a need for studies evaluating the effect of antidepressant treatment approaches on fatigue accompanied by mood disturbance in PSS patients.